Imaging of slow dissociation of the laser induced fragmentation of molecular ions - Gaire, Bishwanath (Kansas State University, 2011)
Lasers are being used widely for the study and manipulation of the dynamics of atomic and molecular targets, and advances in laser technology makes it possible to explore new areas of research — for example attosecond physics. In order to probe the fragmentation dynamics of molecular ions, we have developed a coincidence three-dimensional momentum imaging method that allows the kinematically complete study of all fragments except electrons. Recent upgrades to this method allow the measurement of slow dissociation fragments, down to nearly zero velocity, in intense ultrafast laser fields. Evidences for the low energy breakup are presented using the benchmark molecules diatomic H[subscript]2[superscript]+ and polyatomic H[subscript]3[superscript]+ . The low energy fragments in H[subscript]2[superscript]+ dissociation are due to the intriguing zero-photon dissociation phenomenon. This first experimental evidence for the zero-photon dissociation is further supported by sophisticated theoretical treatment. We have explored the laser pulse length, intensity, wavelength, and chirp dependence of zero-photon dissociation of H[subscript]2[superscript]+, and the results are well described by a two-photon process based on stimulated Raman scattering. Similar studies of the slow dissociation of H[subscript]3[superscript]+ reveal that two-body dissociation is dominant over three-body dissociation. The most likely pathways leading to low-energy breakup into H[superscript]++H[subscript]2, in contradiction to the assessments of the channels in at least one previous study, are explored by varying the laser pulse duration and the wavelength. In addition, we have investigated the dissociation and single ionization of N[subscript]2[superscript]+ , and an interesting high energy feature in addition to the low energy has been observed at higher intensities. Such high energy results from the breakup of molecules in excited states are accessible at higher intensities where their potential energy is changing rapidly with the internuclear distance. We have extended the intense field ionization studies to other molecular ions N[subscript]2[superscript]+ , CO[superscript]+, NO[superscript]+, and O[subscript]2[superscript]+ . The dissociative ionization of these molecules follow a general mechanism, a stairstep ionization mechanism. Utilizing the capability of the upgraded experimental method we have measured the non-dissociative and dissociative ionization of CO[superscript]+ using different pulse lengths. The results suggest that dissociative ionization can be manipulated by suppressing some ionization paths.
Keywords: laser; molecule; dissociation; ionization; Atomic Physics (0748); Molecular Physics (0609); Optics (0752)